2020
DOI: 10.34117/bjdv6n9-204
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação “In Vitro” Da Eficácia Do Extrato Hidroalcoólico Do Cajá (Spondias Mombin L.) E Da Graviola (Annona Muricata L.) Sobre Microorganismos Orais / in Vitro Evaluation of the Efficacy of Cajá (Spondias Mombin L.) and Soursop (Annona Muricata L.) Hydroalcoholic Extract on Oral Microorganisms

Abstract: Avaliação "in vitro" da eficácia do extrato hidroalcoólico do cajá (Spondias mombin L.) e da graviola (Annona muricata L.) sobre microorganismos orais In vitro evaluation of the efficacy of cajá (Spondias mombin L.) and soursop (Annona muricata L.) hydroalcoholic extract on oral microorganisms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
(53 reference statements)
0
0
0
Order By: Relevance
“…These authors demonstrated that this extract inhibited the growth of C. albicans and C. krusei, when used at The hydroethanolic extracts of the bark and fruits of S. mombin were evaluated for their antifungal potential against oral microorganisms, including C. albicans, Candida dubliniensis and C. tropicalis, demonstrating a fungistatic effect at a concentration of 8000 µg/mL. However, unlike the findings of the present research, no fungicidal effect was observed (De Freitas et al 2020).…”
Section: S Ta P H Y Lo C Oc C U S a U R E U S E S C H E R Ic H Ia C O...contrasting
confidence: 55%
See 1 more Smart Citation
“…These authors demonstrated that this extract inhibited the growth of C. albicans and C. krusei, when used at The hydroethanolic extracts of the bark and fruits of S. mombin were evaluated for their antifungal potential against oral microorganisms, including C. albicans, Candida dubliniensis and C. tropicalis, demonstrating a fungistatic effect at a concentration of 8000 µg/mL. However, unlike the findings of the present research, no fungicidal effect was observed (De Freitas et al 2020).…”
Section: S Ta P H Y Lo C Oc C U S a U R E U S E S C H E R Ic H Ia C O...contrasting
confidence: 55%
“…A significant number of plant extracts had their antifungal and antibacterial activities demonstrated by previous research (Chaves et al 2018;De Freitas et al 2020;Roumy et al 2020;Samuggam et al 2021). However, this study is the first to report the effectiveness of S. mombin in enhancing the antibacterial activity of conventional antibiotics against resistant bacteria.…”
Section: Introductionmentioning
confidence: 79%